IRRIGAÇÃO E ADUBAÇÃO NITROGENADANO FEIJOEIRO COMUM CULTIVAR BRS ESTILO - FRANCO, jhonatan da silva,; LOPES, Adriano da Silva,; KRAESKI, Marcos Jefferson,; MEDEIROS, Rosevaldo Domingos,; SILVA, Gustavo Dantas Souza, (ANAIS DO ENIC, 2023)
-